Vloga romskih pomočnikov v Sloveniji pri vključevanju romskih otrok v sistem vzgoje in izobraževanja - Bešter, Romana (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2016)
The article discusses the contribution of Roma assistants to the inclusion of Roma children into the Slovene educational system. Through different approaches and methods we evaluated the work of Roma assistants within the research project titled Together to knowledge, which was going on in the years 2014 to 2015. We focused on: class attendance, cooperation between parents and school, performance of school obligations and command of the Slovene language. The work of Roma assistants in schools and kindergartens has been found useful, necessary and positively accepted on the part of schools, kindergartens and Roma community, having been instrumental in improving the situation in all areas under consideration. School directors and mentors of Roma assistants recognized this institute as highly useful and positive. The key advantage of most Roma assistants as compared to teachers is command of Roma language and culture, which contributes to better communication with Roma children and their parents, and helps to establish mutual trust.
Keywords: Slovenia; Slovenija; romski pomočniki; vzgoja in izobraževanje; Romi